PENGARUH 2iP DAN AIR KELAPA TERHADAP MULTIPLIKASI TUNAS BAWANG MERAH (Allium Ascalonicum L.) KULTIVAR SUMENEP SECARA IN VITRO - Chitra Priatna; Fitri Rachmawati; Diny Dinarti (Jurnal Agroekoteknologi, 2018)
Generative propagation of onion sumenep cultivars had not provided optimum results. To overcome this problem vegetative propagation was used with tissue culture systems. Growth Regulator (ZPT) 2iP and Coconut Water were used as a source of cytokines to stimulate explant. This research was aimed to observe effect of 2iP and coconut water in stimulating red onion compound shoots. This experiment was carried out using a completely randomized design consisting of two factors. The first factor was the provision of 2iP with five levels of concentration of 0.0, 2.0, 4.0, 6.0, 8.0 mg/l and the second factor was the provision of coconut water with three levels of concentration of 10, 20 and 30%. The parameters observed were shoot number, leaf number, leaf length, root number and root length .The results of this research showed that the combination of 8.0 mg/l 2iP and 20% coconut water resulted in an average number of shoots and the highest number of leaves, each of which was 6.5 shoots and 6.3 leaves at 8 MSP. The combination of 2iP treatment and coconut water gave more significant effect than that of the single treatment.